2020
DOI: 10.3390/pharmacy8020087
|View full text |Cite
|
Sign up to set email alerts
|

Association of a Novel Medication Risk Score with Adverse Drug Events and Other Pertinent Outcomes Among Participants of the Programs of All-Inclusive Care for the Elderly

Abstract: Preventable adverse drug events (ADEs) represent a significant public health challenge for the older adult population, since they are associated with higher medical expenditures and more hospitalizations and emergency department (ED) visits. This study examines whether a novel medication risk prediction tool, the MedWise Risk Score™ (MRS), is associated with ADEs and other pertinent outcomes in participants of the Programs of All-Inclusive Care for the Elderly (PACE). Unlike other risk predictors, this tool pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(44 citation statements)
references
References 45 publications
3
41
0
Order By: Relevance
“…In older adults with polypharmacy, this hypothetical increase in MRS TM was primarily associated with an increase in CYP450 drug interaction burden and drug-induced LQTS scores. The MRS TM has been previously evaluated and validated in a sub-cohort of PACE participants as a medication risk prediction tool for ADE and medical outcomes including hospitalization, emergency department visits, and medical expenditure [21]. Bankes et al reported that each point increase in the MRS TM was significantly associated with an increase of ADE (OR = 1.09), additional emergency visits (+3 visits/ 100 patients/year), and an extra yearly medical expenditure of $1037.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In older adults with polypharmacy, this hypothetical increase in MRS TM was primarily associated with an increase in CYP450 drug interaction burden and drug-induced LQTS scores. The MRS TM has been previously evaluated and validated in a sub-cohort of PACE participants as a medication risk prediction tool for ADE and medical outcomes including hospitalization, emergency department visits, and medical expenditure [21]. Bankes et al reported that each point increase in the MRS TM was significantly associated with an increase of ADE (OR = 1.09), additional emergency visits (+3 visits/ 100 patients/year), and an extra yearly medical expenditure of $1037.…”
Section: Discussionmentioning
confidence: 99%
“…A medication risk stratification was used to simulate the impact of different COVID-19 repurposed drugs on the MRS™ (see the Patent section of the manuscript for more details) [21][22][23]30]. The total MRS TM and the individual aggregated risk factors (FDA Adverse Event Reporting System (FAERS), anticholinergic cognitive burden (ACB), sedative burden (SB), drug-induced LQTS, and CYP450 drug interaction burden scores) were divided into sub-categories of Low risk, Moderate risk, and High risk.…”
Section: Medication Risk Score and Simulation Strategymentioning
confidence: 99%
See 2 more Smart Citations
“…Although this may represent a preferred clinical strategy, the administration of two or more drugs at overlapping times increases the likelihood of drug-drug interactions [1,2]. As the risk of drug-drug interactions increases, the risk of debilitating, even fatal, adverse drug events also increases [3]. From a pharmacokinetics standpoint, drug-drug interactions occur when one drug-the perpetrator drug-alters the disposition of another co-administered drug-the victim drug.…”
Section: Introductionmentioning
confidence: 99%